Hidden Stories, Toxic Stories, Healing Stories:: The Power of Narrative in Peace and Reconciliation - Marks, Stephan (Narrative Matters)

(untitled) (The University of New Brunswick, 2011)
Research on narrative is more than simply listening to (more or less) nice stories. There are stories that are hidden between the lines; these need to be noticed and retrieved. There are stories that can be toxic to be exposed to; these need to be coped with and conceived. But there may be stories that have a healing quality, too—stories that can contribute to peace and reconciliation. These three possible qualities of narratives are the focus of the following paper, which was delivered in October 2008, at the launch of the Centre for Interdisciplinary Research on Narrative at St. Thomas University in Fredericton, New Brunswick, Canada. The lecture was based on his interdisciplinary research project "Geschichte und Erinnerung" [History and Memory, www.geschichte-erinnerung.de] in which interviews with Nazi followers, bystanders, and perpetrators were conducted and analysed. Marks presented one of the key findings of this research—shame—and its effect on what the interviewees recounted, as well as its relevance for National Socialism and present-day German society.